On the need for regional climate information over Africa under varying levels of global warming. (4th June 2018) - Lennard, C J; Nikulin, G; Dosio, A; Moufouma-Okia, W
Abstract: The Paris Agreement of COP21 set a goal of holding global average temperature increases to below 2 °C above pre-industrial levels and to pursue efforts to limit the temperature increase to 1.5 °C. This is particularly relevant for the African context where temperatures are likely to warm faster than the global average and where the magnitude of change will be regionally heterogeneous. Additionally, many biogeophysical and socioeconomic systems are particularly vulnerable to change in both means and extremes. In this paper we contextualise the lack of regional climate information over Africa at global warming levels (GWLs) of 1.5 and 2 °C above pre-industrial levels through a short review of the literature. We show most studies that provide information over Africa under specific GWLs have used data from global models, however global models poorly resolve local scale forcing (e.g. topography) nor the internal climate variability of a region. Although downscaling using regional climate models can address these issues we find only one paper that has used downscaled data for GWL studies over Africa. Articles in this focus collection use data from global climate models and the co-ordinated regional downscaling experiment to elucidate the regional and local scale climate responses to various warming levels. This may provide information that contributes meaningfully to the UNFCCC negotiation process and also for the development of adaptation and mitigation policies.